Individual-based multiscale model for foot-and-mouth disease - Mufoya, Blessings; Mathebula, Dephney; Garira, Winston (Frontiers in Applied Mathematics and Statistics, 2025)
The study of infectious disease dynamics across various hierarchical levels and scales of organization has gained significant attention in the realm of mathematical biology. We develop an individual-based network multiscale model of foot-and-mouth disease (FMD) in cattle based on the replication-transmission relativity theory at whole living organism level. An important feature of individual-based network multiscale models is that they incorporate heterogeneity in [i.] host susceptibility to infection, [ii.] the ability of hosts to transmit pathogen to other hosts, [iii.] host immune response, and [iv.] host behaviour. Numerical simulations are conducted to demonstrate the influence of model parameters designated for controlling, eliminating, and eradicating FMD. Results indicate that microscale parameters such as the clearance rate of virus, ωi and the macroscale parameters like the transmission rate between the cattle, βij are crucial for implementing interventions (vaccination and quarantine respectively). Additionally, the analysis of the network degree distribution indicates the absence of hubs due to lack of a heavy tail on the histogram.